REPOSITIONING THE SOUTH EAST OF NIGERIA FOR SUSTAINABLE SOCIO-ECONOMIC DEVELOPMENT - Alozie, Cyprian C. (African Journal of Social and Behavioural Sciences, 2024)
This paper focused on the repositioning of the Southeast zone of Nigeria for sustainable socioeconomic development in the 21st century. Recent discoveries have shown that the area that once flourished economically have been suffering some level of decay and desertion due to a number of security-related factors and infrastructural challenges. The objective of this paper is therefore to investigate the strategic options to be undertaken in order to reposition the South East Zone for socioeconomic development. Adopting the theory of social solidarity, the paper argues that the series of agitations expressed by people of the zone over their alleged marginalization by the federal government has continued to attract national and even international solidarity in their favour. Methodologically, materials for the study were sourced through secondary means of data collection whereas the content method was applied in the analysis. The study discovered that there has been a decline in the pace of economic activities in the South East zone due to a number of factors. The study recommends that the various levels of government in the country should do all within their powers to improve security in the South East zone and provide an enabling environment to enable the zone be repositioned for sustainable socioeconomic development.